A New Near Optimal Harmonics Elimination PWM Algorithm For AC Traction Drives - Salam, Zainal; Chew, Tit Lynn (Penerbit UTM Press, 2002)
For AC traction system, it is necessary to develop voltage source inverters (VSI) which is compatible with existing types of signaling systems adopted by various railway operators. The varying harmonics incidents of conventional sinusoidal-type PWM VSI is not particularly suitable as it produces unwanted harmonics within the signaling frequency band. One well-known solution to ensure that the unwanted harmonics do not appear on the spectra is by using the harmonics elimination PWM (HEPWM) switching method. However, the application of HEPWM has been somewhat limited by the fact that the switching angles cannot be calculated online by a microprocessor-based waveform generator. This is due to the fact that the equations involved are non-linear and transcendental in nature. The paper presents an algorithm to calculate near optimal switching angles, which will permit a fast and efficient realization using a microprocessor. The method is based on quadratic approximation approach which is derived from the computed trajectories of angles.